The Relationship Between Obsessive-Compulsive Symptoms and Dissociation: A Systematic Review and Meta-Analysis. Issue 3 (27th May 2023) - Sideli, Lucia; Santoro, Gianluca; Fontana, Andrea; Guglielmucci, Fanny; Caretti, Vincenzo; Schimmenti, Adriano
ABSTRACT: This systematic review and meta-analysis aimed to investigate the relationship between dissociation and obsessive-compulsive symptoms (OCS) and disorder (OCD). Specifically, the study aimed to (a) estimate the pooled prevalence of dissociative disorders among individuals with OCD; (b) systematically review the prevalence of OCD among individuals with dissociative disorders; (c) compare the severity of dissociative symptoms between individuals with OCD and non-clinical controls; (d) estimate the association between OCS and dissociative symptoms in the clinical and non-clinical populations. A systematic search was carried out in biomedical databases from inception to January 2022 according to PRISMA guidelines. A total of 41 studies met inclusion criteria ( n = 9, 438, 34.3% males). The pooled prevalence of dissociative disorders in adult samples with OCD was 8% (95% CI [3, 15], k = 5). Studies on adolescent and adult patients with dissociative disorders found that 17–32% reported comorbid OCD, while a prospective study of patients with early-onset dissociative disorders found no evidence of association with OCD. Individuals affected by OCD reported more dissociative symptoms than non-clinical controls ( g = .67, 95% CI [.18, 1.16], k = 9). A moderate correlation between dissociative symptoms and OCS was detected ( r = .43, 95% CI [.36, .51], k = 18). Sensitivity analyses showed small/moderate correlations between dissociative experiences and specific types of obsessions and compulsions. Findings suggest that dissociative symptoms are moderately related to OCS in both clinical and non-clinical populations. Interventions aimed to reduce dissociation might improve treatment response of patients suffering from OCD.